PENGARUH KEADILAN ORGANISASIONAL, KEPEMIMPINAN TRANSFORMASIONAL, DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL PADA KARYAWAN PT. AIRA GIBRA INTERNUSA BEURADEN ACEH BESAR - G., Harbiyah; Fitri, Aida (Fakultas Ekonomi, 2024)
This research aims to determine the influence of organizational justice, transformational leadership and job satisfaction on organizational commitment in PT employees. Aira Gibra Internusa Beuraden Aceh Besar. This research is quantitative research using primary data in the form of questionnaires for data collection, and secondary data in the form of literature study. The population in this study is all employees who work at PT. Aira Gibra Internusa Beuraden Aceh Besar has 135 employees. The sample was taken using the Slovin technique as many as 57 employees, using random sampling techniques. The data analysis technique in this research is to use multiple linear regression analysis with validity and reliability tests first carried out. To see whether there is an influence between the independent and dependent variables, the t-test is partially used. The results of data processing from multiple linear regression analysis show that there is a positive influence of organizational justice, transformational leadership, and job satisfaction on organizational commitment.Keywords:Organizational Justice, Transformational Leadership, Job Satisfaction, Organizational Commitment